GJB2 mutations and degree of hearing loss : a multicenter study - Snoeckx, RL; Huygen ,PL; Feldmann, D; Marlin, S; Denoyelle, F; Waligora, J; Mueller-Malesinska, M; Pollak, A; Ploski, R; Murgia, A; Orzan, E; Castorina, P; et al. (American journal of human genetics, 2005)
Hearing impairment (HI) affects 1 in 650 newborns, which makes it the most common congenital sensory impairment. Despite extraordinary genetic heterogeneity, mutations in one gene, GJB2, which encodes the connexin 26 protein and is involved in inner ear homeostasis, are found in up to 50% of patients with autosomal recessive nonsyndromic hearing loss. Because of the high frequency of GJB2 mutations, mutation analysis of this gene is widely available as a diagnostic test. In this study, we assessed the association between genotype and degree of hearing loss in persons with HI and biallelic GJB2 mutations. We performed cross-sectional analyses of GJB2 genotype and audiometric data from 1,531 persons, from 16 different countries, with autosomal recessive, mild-to-profound nonsyndromic HI. The median age of all participants was 8 years; 90% of persons were within the age range of 0-26 years. Of the 83 different mutations identified, 47 were classified as nontruncating, and 36 as truncating. A total of 153 different genotypes were found, of which 56 were homozygous truncating (T/T), 30 were homozygous nontruncating (NT/NT), and 67 were compound heterozygous truncating/nontruncating (T/NT). The degree of HI associated with biallelic truncating mutations was significantly more severe than the HI associated with biallelic nontruncating mutations (P<.0001). The HI of 48 different genotypes was less severe than that of 35delG homozygotes. Several common mutations (M34T, V37I, and L90P) were associated with mild-to-moderate HI (median 25-40 dB). Two genotypes--35delG/R143W (median 105 dB) and 35delG/dela(GJB6-D13S1830) (median 108 dB)--had significantly more-severe HI than that of 35delG homozygotes.
Keywords: audiometrie; Audiometry; geny recesivní; předškolní dítě; retrospektivní studie; Mutation; Child; novorozenec; konexiny; Humans; lidé; Homozygote; alely; heterozygot; Retrospective Studies; mladiství; lidé středního věku; Heterozygote; Gene Frequency; frekvence genu; Alleles; Middle Aged; Female; Male; Hearing Loss; Adult; Infant, Newborn; mutace; DNA Mutational Analysis; Genes, Recessive; lineární modely; kojenec; mužské pohlaví; Linear Models; Aged; mutační analýza DNA; Infant; ženské pohlaví; multicentrické studie jako téma; Cross-Sectional Studies; homozygot; Severity of Illness Index; průřezové studie; Child, Preschool; stupeň závažnosti nemoci; dospělí; dítě; nedoslýchavost; Multicenter Studies as Topic; Connexins; Adolescent; senioři